Can interestingness measures be usefully visualized? - Susmaga, Robert; Szczęch, Izabela (Zielona Góra: Uniwersytet Zielonogórski)
The paper presents visualization techniques for interestingness measures. The process of measure visualization provides useful insights into different domain areas of the visualized measures and thus effectively assists their comprehension and selection for different knowledge discovery tasks. Assuming a common domain form of the visualized measures, a set of contingency tables, which consists of all possible tables having the same total number of observations, is constructed.
Keywords: visualization; interestingness measures; confirmation measures; barycentric coordinates